Willingness to use a supervised injection facility among young adults who use prescription opioids non-medically: a cross-sectional study. Issue 1 (December 2017) - Bouvier, Benjamin; Elston, Beth; Hadland, Scott; Green, Traci; Marshall, Brandon
Abstract Background Supervised injection facilities (SIFs) are legally sanctioned environments for people to inject drugs under medical supervision. SIFs currently operate in ten countries, but to date, no SIF has been opened in the USA. In light of increasing overdose mortality in the USA, this study evaluated willingness to use a SIF among youth who report non-medical prescription opioid (NMPO) use. Methods Between January 2015 and February 2016, youth with recent NMPO use were recruited to participate in the Rhode Island Young Adult Prescription Drug Study (RAPiDS). We explored factors associated with willingness to use a SIF among participants who had injected drugs or were at risk of initiating injection drug use (defined as having a sex partner who injects drugs or having a close friend who injects). Results Among 54 eligible participants, the median age was 26 (IQR = 24–28), 70.4% were male, and 74.1% were white. Among all participants, when asked if they would use a SIF, 63.0% answered "Yes", 31.5% answered "No", and 5.6% were unsure. Among the 31 participants reporting injection drug use in the last six months, 27 (87.1%) reported willingness to use a SIF; 15 of the 19 (78.9%) who injected less than daily reported willingness, while all 12 (100.0%) of the participants who injected daily reported willingness. Compared to participants who were unwilling or were unsure, participants willing to use a SIF were also more likely to have been homeless in the last six months, have accidentally overdosed, have used heroin, have used fentanyl non-medically, and typically use prescription opioids alone. Conclusions Among young adults who use prescription opioids non-medically and inject drugs or are at risk of initiating injection drug use, more than six in ten reported willingness to use a SIF. Established risk factors for overdose, including homelessness, history of overdose, daily injection drug use, heroin use, and fentanyl misuse, were associated with higher SIF acceptability, indicating that young people at the highest risk of overdose might ultimately be the same individuals to use the facility. Supervised injection facilities merit consideration to reduce overdose mortality in the USA.